Antibodies@MOFs: An In Vitro Protective Coating for Preparation and Storage of Biopharmaceuticals. Issue 2 (27th November 2018) - Feng, Yifan; Wang, Huanrong; Zhang, Sainan; Zhao, Yu; Gao, Jia; Zheng, Yunyi; Zhao, Peng; Zhang, Zhenjie; Zaworotko, Michael J.; Cheng, Peng; Ma, Shengqian; Chen, Yao
Abstract: Antibodies have emerged as a fast‐growing category of biopharmaceuticals that have been widely applied in scientific research, medical diagnosis, and disease treatment. However, many antibodies and other biopharmaceuticals display inferior biophysical properties, such as low stability and a propensity to undergo aggregation. Enhancing the stability of biopharmaceuticals is essential for their wide applications. Here, a facile in vitro protective coating strategy based on metal–organic frameworks (MOFs) is proposed to efficiently protect antibodies against perturbation environments and quickly recover them from the MOFs before usage, which avoids introducing protective additives into the body, which may cause biosafety risks. The protected antibodies exhibit extraordinary thermal, chemical, and mechanical stabilities, and they can survive for long‐term storage (>3 weeks) under severe temperature variation (4 ↔ 50 °C) at a fast ramp rate (25 °C min −1 ). More importantly, the encapsulated antibodies can be easily released as quickly as 10 s with high efficiency (≈100%) to completely remove the MOFs before use. This study paves a new avenue for the facile preparation and storage of biopharmaceuticals represented by antibodies under ambient or perturbation conditions, which may greatly broaden and promote the applications of both MOFs and biopharmaceuticals. Abstract : The use of metal–organic frameworks (MOFs) as removable shells with a prominent protection effect, for the preparation and storage of antibodies, by a facile and efficient strategy is demonstrated. The encapsulated antibodies can be quickly recovered from the MOFs before use, which avoids introducing protective additives into the body, which may otherwise cause biosafety risks. This study reveals that MOFs have great potential to serve as versatile platforms for preparation and storage of biopharmaceuticals.